2022
DOI: 10.1155/2022/6215282
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Predictive Effect of Lactic Acid Combined with Cardiac Troponin T and 5‐Hydroxytryptophan on the Severity of Sepsis in ICU Patients and Its Correlation with Prognosis

Abstract: In order to explore the effective markers of presepsis in the prediction of clinical disease and disease severity, the predictive effect of lactic acid (Lac) combined with cardiac troponin T (cTnT) and 5-hydroxytryptophan (5-HT) on the severity of sepsis in intensive care unit (ICU) patients and its correlation with prognosis is investigated. A total of 85 sepsis patients admitted to the ICU of our hospital from January 2020 to June 2021 are selected to establish the ICU sepsis group, and 72 health examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Определение комбинации сывороточных показателей: лактата, cTnT и 5-гидрокситриптофана -имеет высокую прогностическую ценность для выявления состояния пациентов с сепсисом, а также прогноза тяжести заболевания. Клинический мониторинг этих показателей позволяет оптимизировать схему терапии [92].…”
Section: тропонинunclassified
“…Определение комбинации сывороточных показателей: лактата, cTnT и 5-гидрокситриптофана -имеет высокую прогностическую ценность для выявления состояния пациентов с сепсисом, а также прогноза тяжести заболевания. Клинический мониторинг этих показателей позволяет оптимизировать схему терапии [92].…”
Section: тропонинunclassified
“…The combination of serum markers -lactate, cTnT, and 5-hydroxytryptophan -has a high prognostic value for assessing the sepsis condition and the course of the disease. Clinical monitoring of these indicators allows for optimization of the therapy regimen [96].…”
Section: Troponinmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%